2014
DOI: 10.1007/s11661-014-2493-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation on the Evolution of Shear Banding and Buckling in Tungsten Fiber Reinforced Zr-Based Bulk Metallic Glass Composite

Abstract: The evolution of micro-damage and deformation of each phase in the composite plays a pivotal role in the clarification of deformation mechanism of composite. However, limited model and mechanical experiments were conducted to reveal the evolution of the deformation of the two phases in the tungsten fiber reinforced Zr-based bulk metallic glass composite. In this study, quasi-static compressive tests were performed on this composite. For the first time, the evolution of micro-damage and deformation of the two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…However, the dynamic yield strength Y p of the high-density WF/Zr-MG is 3000 MPa, which is higher than that of 93W alloy with a strain rate of 3000 s − 1 . According to equation (7), it can be found that the penetration velocity u of the highdensity WF/Zr-MG composite penetrator is larger than that of the 93W alloy penetrator when these penetrators have the same velocity v. In other words, the penetration ability of the high-density WF/Zr-MG composite penetrator is better than that of the 93W alloy penetrator with the same penetration conditions, such as mass and impact velocity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the dynamic yield strength Y p of the high-density WF/Zr-MG is 3000 MPa, which is higher than that of 93W alloy with a strain rate of 3000 s − 1 . According to equation (7), it can be found that the penetration velocity u of the highdensity WF/Zr-MG composite penetrator is larger than that of the 93W alloy penetrator when these penetrators have the same velocity v. In other words, the penetration ability of the high-density WF/Zr-MG composite penetrator is better than that of the 93W alloy penetrator with the same penetration conditions, such as mass and impact velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its excellent properties, including high-density and high-dynamic compressive strength, the tungsten fiber reinforced Zr-based metallic glass (Zr 41.25 Ti 13.75 Cu 12.5 Ni 10 Be 22.5 ) matrix (WF/Zr-MG) composite is considered as a potential new generation of projectile material to replace DUA and WHA [6,7]. Lots of research on WF/Zr-MG composite, which covers material design and preparation, fracture mode, and static and dynamic mechanical properties, have been reported in the past few years [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10(b), it can be seen that the splitting fracture always happens within the tungsten fiber. In our other work (Chen et al, 2014), the deformation process of this composite is investigated carefully. It was found that the splitting initiate within the tungsten fiber near the fiber/matrix interface region.…”
Section: Quasi-static Compressive Testsmentioning
confidence: 99%
“…Thermal residual stress in the W fiber was established to be under compressive stress state in the three-dimensional (3D) directions, which is beneficial to the performance improvement of the W f /BMGCs [16,17]. It was found that the W fibers yielded firstly and then transferred load to the metallic glass phase during deformation, the bonding characteristics and the interfacial status between the two phases are the key factors to determine whether the W f /BMGCs shear or split [18][19][20][21]. In addition, the failure mode of the W f /BMGCs is influenced seriously by W fiber volume fraction (V f ), the failure mode varied from shearing to longitudinal splitting with the increase of V f [22][23][24].…”
Section: Introductionmentioning
confidence: 99%